Enhancing the Accuracy of Pedicle Screw Placement Using 3D-Printed Screw-Guiding Techniques in the Lumbosacral Region for Small Breed Dogs: A Cadaveric Study - Jin-Yeong Kim; Ho-Hyun Kwak; Heung-Myong Woo; Junhyung Kim (Animals)
A 3D-printed guide is an effective method for accurately placing pedicle screws in dog vertebrae. While a conventional drill guide allows precise pilot hole formation, it can lead to potential screw wobbling during insertion. In this study, we applied a technique that assists with both drilling and screw insertion, and we compared the accuracy of screw placement using this approach with that achieved by the conventional drill guide. The screws were divided into three groups: Group A (drill guide), Group B (cannulated guide), and Group C (screw guide). The accuracy of screw placement was assessed by comparing preoperative and postoperative CT images. Group A exhibited the largest angular deviation. Group C exhibited significantly smaller deviations in entry point, exit point, angle α, and angular deviation than Group A. In Group B, only the exit-point deviation was significantly smaller than that in Group A. Furthermore, the angular deviation in Group C was significantly smaller than that in Group B. In conclusion, 3D-printed screw-guiding techniques improved the accuracy of pedicle screw placement, with screw guides outperforming cannulated guides, making them a viable option for small breed dogs.